Consecuencias metabólicas e inmunológicas de la inducción de la actividad de HIF-1a [alfa] en linfocitos T CD4+ infectados con VIH-1 - Duette, Gabriel (2019)
Chronic immune activation and inflammation are hallmarks of HIV-1 infection and a major cause of serious non-AIDS events in HIV-1-infected individuals on antiretroviral treatment (ART). Herein, we show that cytosolic double-stranded DNA (dsDNA) generated in infected CD4T cells during the HIV-1 replication cycle promotes the stabilization of the transcription factor hypoxia-inducible factor 1? (HIF-1?), which in turn, enhances viral replication. Furthermore, we show that induction of HIF-1? promotes the release of extracellular vesicles (EVs). These EVs foster inflammation by inducing the secretion of gamma interferon by bystander CD4+ T cells and secretion of interleukin 6 (IL-6) and IL-1? by bystander macrophages through an HIF-1?-dependent pathway. Remarkably, EVs obtained from plasma samples from HIV-1-infected individuals also induced HIF-1? activity and inflammation. Overall, this study demonstrates that HIF-1? plays a crucial role in HIV-1 pathogenesis by promoting viral replication and the release of EVs that orchestrate lymphocyte- and macrophage mediated inflammatory responses.